Left ventricular remodelling types in elderly patients with arterial hypertension - L. Kh. Gadzhieva; K. A. Masuev; M. I. Ibragimova (Российский кардиологический журнал)
Aim. To study left ventricular (LV) remodelling types and their association with age, gender, duration of arterial hypertension (AH), and cardiac arrhythmias in elderly patients with Stage II–III AH. Material and methods. The study included 80 AH patients (23 men, 57 women) with different levels of cardiovascular risk (age 60–86 years; mean age 72,4±6,5 years). The mean AH duration was 19,6±6,8 years. All participants underwent echocardiography and long-term ECG monitoring. Statistical analyses were performed using “Statistica-6.0” software (StatSoft Inc., 1984–2001). Results. In the study sample of elderly AH patients, the following geometricLV models were registered: concentricLV remodelling (n=30, 37,5%), concentricLV hypertrophy (n=36, 45,0%), and eccentricLV hypertrophy (n=36, 45,0%). The most prevalent cardiac arrhythmia was the combination of supraventricular (SVE) and ventricular (VE) extrasystoles, particularly in patients with concentricLV hypertrophy. In this group, atrial fibrillation was also prevalent. The second most prevalent cardiac arrhythmia was SVE, with the highest prevalence in patients with concentricLVremodelling. Conclusion. Elderly patients with Stage II–III AH were characterised by the high prevalence of concentricLV hypertrophy. This clinical group had the highest levels of cardiovascular risk, as well as the highest prevalence of cardiac arrhythmias, including arrhythmias with poor prognosis. Echocardiographic parameters ofLV remodelling were similar in patients aged 60–74 vs. 75+ years. There was a weak, albeit statistically significant, association betweenLV remodelling type and AH duration.